MANAJEMEN RESIKO PADA PELAKSANAAN PROYEK KONSTRUKSI - abd karim hadi; Elka Buhaemi (UNDERPASS Journal of Civil Engineering, Applied Sciences, and Technology, 2022)
Risk management is a method that is arranged logically and systematically from a series of activities: setting the context, identifying, analyzing, evaluating, controlling and communicating risks. The concept of risk management was introduced in the field of occupational safety and health in the 1980s after the development of the accident model theory from ILCI and also the rise of environmental and health issues. expected hazard that is a threat to the property and financial gain resulting from the hazard. Risk management is an approach taken to risk by understanding, identifying and evaluating the risks of a project. The purpose of this study is to find out about risk management in construction projects. The method used is a literature study on risk management in construction projects with reference to relevant theories. The study results show that risk management is very important for every construction project to avoid losses in cost, quality and project completion schedule. Take actions to deal with risks that may occur (risk response) by means :  withhold  risk   (risk retention), reducing risk (risk reduction), transferring risk (risk transfer), avoiding risk (risk avoidance).